The daily living experience of nursing woman-workers that display work related musculoskeletal disorders (WRMD) at optical heideggerian existential phenomenology - Patrícia Campos Leite; Miriam Aparecida Barbosa Merighi; Arlete - Silva (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
In this qualitative study of phenomenologic approach, I have searched for understanding the living experience of nursing woman-workers that display work related musculoskeletal disorders (WRMD). The interviews were carried out with six women who were living the WRMD, four being auxiliary and two technicians in nursing. In order to disclose the essence of the phenomenon being a nursing woman-worker living the WRMD, I have developed the following guiding question: I would like you to tell me about your experience such as what it means to you to be a woman, worker in nursing enduring a work related musculoskeletal disorders? All questions were analyzed under the enlightenment of the philosophical referential of Martin Heidegger. The results of this study display the trajectory went through by the woman-workers that became sick due to WRMD, and so glimmering ways to an authentic care by a chronic and incapacitating disease of preoccupying character public health in Brazil.